Modernism, neopopulism and a problem of the Jewish identity in the Russian Empire in the early twentieth century - Bezarov, O. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
Abstract Introduction. Identity crisis which was a consequence of socio-cultural and economic contradictions in modern European society in the late nineteenth century, has caused the need of formation the alternative spheres of knowledge (Marxism, Freudianism and Nietzscheanism). Practical forms of transformation of social reality (terrorism, nationalism and revolutionary) became necessary. The crisis was a real trial, because it wasn’t a single model of overcoming which could be considered effective (assimilation or the revolutionism) in condition of the Romanov imperial nationalism. As Russian Populism did not contain features of Russian ethnic nationalism, we can assume that promoted the ideology of revolutionary populists socialism could be used by the marginal Russian-Jewish intelligentsia as one of the ways to overcome the crisis of the Jewish identity. As Russian Populism didn’t contain features of Russian ethnic nationalism, we can assume that the ideology of revolutionary socialism, promoted by neopopulists, could be used by the marginal Russian-Jewish intelligentsia as one of the ways to overcome the crisis of the Jewish identity. Purpose. Identify the relationship of development of neopopulism and the processes of modernization Late Imperial Russia, and also to analyze the possible ways of overcoming the crisis of Jewish identity within the ideology of revolutionary socialism. Results. After the the regicide on March 1, 1881, the confrontation between autocracy and revolutionary populists led to the rising a wave of political terrorism which was prevalent primarily in the southwest of the Russian Empire in the early twentieth centure. Active participation of the Jewish youth in neopopulist organizations emphasized political attractiveness of the ideas of revolutionary socialism, especially among assimilated Russian-Jewish intelligentsia. Some members of such organizations tried to counter the ideology of Jewish nationalism (Zionism) to the Jewish revolutionary strategy. As the revolutionary Jewish marginals within the neopopulist movement (which was led by Socialist-Revolutionary Party), it was suggested to Russian Jews the saving of their national identity. The leaders of the influential political organization, which declared a war autocracy, were representatives of the radical Russian-Jewish intelligentsia. Originality. Neopopulism as a revolutionary ideology of Russian-Jewish intelligentsia tried to save Jews assimilated generation,which numerous members hoped to escape the national suicide for the proving their imperial loyalty, as required by the policy of modernization. But anti-Semitism and the Pogroms revealed the absurdity of such loyalty tactics by Russian Jews. Conclusion. The bulk of small-town Jews became a «nutritious ground» for recruiting staff in the neopopulist revolutionary group, but which, instead, remained very ignorant and rather superstitious as to Russian-Jewish revolutionary intelligentsia was able to offer own way "out of the ghetto". Ideology of the revolutionary socialism, which was presented, for example in the views of S. Rappoport (An-sky) and H. J. Zhytlovskoho, proved the painful searching of new models of Jewish identity in the revolutionary area that of the downfall Russian Empire by well-known representatives of the Jewish neopopulism. Obviously, the risks of searching were rather dangerous in its political consequences, therefore, caution with which the Jewish neopopulists have advanced their ideas, they often strucked up in a deadlock or, in the case of E. F. Azef, became an example of peculiar metamorphoses of Jewish revolutionary.